An iterative solution approach for steady state analysis of self-excited induction generator. (1st August 2019) - Arabaci, Hayri
The steady state analysis of self-excited induction generator is widely used for stand-alone renewable energy system. The impedance values of equivalent circuit vary depending on frequency. The frequency changes according to load, excitation capacitance and rotor speed. If the values of load and capacitance are known, only the frequency and slip are the two main unknowns left for analysis of the single-phase equivalent circuit. The simulation is generally performed for a desired slip value to obtain the frequency. However, with the proposed approach in this study, the values of rotor slip, and frequency of terminal voltage are both directly determined in shorter time. The proposed algorithm is verified by the experiments of three phase 1.1 kW squirrel cage induction machine.